Building Supply Chain Leaders in Creating Business Performance: A Rasch Model Approach - Herlina, Maria Grace; Lasmy, Lasmy; Sudrajat, Darjat; Syahchari, Dicky Hida; Saroso, Hardijanto (ExcelingTech, 2020)
The logistics and supply chain is an emerging business in the world. As the